2021
DOI: 10.3390/chemosensors9110323
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Voltammetric Screening Method for the Assessment of Bioflavonoid Content Using the Disposable Bare Pencil Graphite Electrode

Abstract: Hesperidin (HESP) is a plant bioflavonoid found in various nutritional and medicinal products. Many of its multiple health benefits rely on the compound’s antioxidant ability, which is due to the presence of oxidizable hydroxyl groups in its structure. Therefore, the present study aimed to investigate the electrochemical behavior of HESP at a cheap, disposable pencil graphite electrode (PGE) in order to develop rapid and simple voltammetric methods for its quantification. Cyclic voltammetric investigations emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The tested working electrodes were different hardness, with PGEs of 0.50 mm graphite pencil leads (B, HB and 2B from the brands Laco and Rotring) having the geometrical active surface area (A g ) of 0.1589 cm 2 ; a glassy carbon electrode (GCE) and a Pt electrode with the A g of 0.0700 cm 2 and 0.0314 cm 2 , respectively. Nevertheless, the main working electrode was the PGE, which consisted of 6.00 cm long, commercially available graphite pencil leads cut in half and introduced with the cut edge into a mechanical pencil lead used as a holder; 1.50 cm of the lead remained outside and always only 1.00 cm of this part was immersed in the analyzed solution so that the A g of the electrode was always constant [ 41 ]. The electrical contact was realized by a copper wire soldered on the metallic part of the pencil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested working electrodes were different hardness, with PGEs of 0.50 mm graphite pencil leads (B, HB and 2B from the brands Laco and Rotring) having the geometrical active surface area (A g ) of 0.1589 cm 2 ; a glassy carbon electrode (GCE) and a Pt electrode with the A g of 0.0700 cm 2 and 0.0314 cm 2 , respectively. Nevertheless, the main working electrode was the PGE, which consisted of 6.00 cm long, commercially available graphite pencil leads cut in half and introduced with the cut edge into a mechanical pencil lead used as a holder; 1.50 cm of the lead remained outside and always only 1.00 cm of this part was immersed in the analyzed solution so that the A g of the electrode was always constant [ 41 ]. The electrical contact was realized by a copper wire soldered on the metallic part of the pencil.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years PGE gained increasing applicability due to its similar or even better electrochemical characteristics in comparison to other commonly used working electrodes, besides its other inherent economic advantages (cost-effectiveness and easy availability) [ 35 , 36 ]. However, there are few reports using this electrode for the electroanalysis of bioflavonoids [ 34 , 37 , 38 , 39 , 40 , 41 ] which, based on their oxidation potential [ 42 ], are considered to have intermediate antioxidant power (AOP) [ 43 ]. To the best of our knowledge, there is no research that has been conducted on the NG electroanalysis of disposable, bare PGE.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, pencil graphite electrodes are recognized as attractive electrode substrates owing to their low cost, simplicity, and commercial availability, and have been used for the detection of different analytes [ 17 ]. For example, several studies have reported the use of pencil graphite electrodes (bare or treated) for the sensitive detection of bioflavonoids such as quercetin [ 18 ], diosmin [ 19 ], and hesperidin [ 20 , 21 ]. Particularly, David et al reported the electrocatalysis of hesperidin at pencil graphite electrodes with different hardness (from 2B to 2H) [ 21 ] although the detailed effects of the surface morphology and the characterization of pencil graphite electrodes on the electrocatalysis of hesperidin remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have reported the use of pencil graphite electrodes (bare or treated) for the sensitive detection of bioflavonoids such as quercetin [ 18 ], diosmin [ 19 ], and hesperidin [ 20 , 21 ]. Particularly, David et al reported the electrocatalysis of hesperidin at pencil graphite electrodes with different hardness (from 2B to 2H) [ 21 ] although the detailed effects of the surface morphology and the characterization of pencil graphite electrodes on the electrocatalysis of hesperidin remains unclear. Furthermore, a portable microelectrochemical sensor based on pencil graphite for rapid bioflavonoids detection has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…A promising approach in pharmaceutical analysis can be the use of electroanalytical techniques, especially due to the fact that they are suitable for miniaturization and portability, thus enabling on-site monitoring. Their efficiency was proven by their extensive use for the detection and quantification of various compounds, with powerful impacts on human health [2][3][4][5] and environment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%